Mechanistic Insights into The Catalytic Esterification of Acetic Acid with Crude Glycerol - Olet, Victor (Curtin University, 2024)
This thesis investigates the reaction mechanism of catalytic esterification of crude glycerol with acetic acid, by obtaining isomeric ester yields and conducting selectivity analyses. Computational quantum techniques are employed to analyse local reactivity, reaction complex stability, and overall activation energy for each esterification pathway. The impact of methanol addition, water addition, and the effect of heterogeneous catalysis is also studied, providing valuable design considerations into the esterification of fast pyrolysis bio-oil with crude glycerol.